A influência da sindicalização dos professores no desempenho escolar dos alunos no Brasil no período de 1995 a 2005 - Landwehrkamp , Daniel (2010)
This work discusses the influence of 4th and 8th grade elementary school teachers that became union members in the student performance, as well as the 3rd grade of the high school in Brazil from 1995 until 2005, having as theorical reference foreign literature about the subject, mainly coming from the United States, as the studies in Brazil about this subject are still at the beginning phase. This is why this work will contribute with the education research field. This work was based on microdata from the SAEB – Sistema Nacional de Avaliação da Educação Básica, Elementary School National Evaluation System and data from PNAD – Pesquisas Nacionais por Amostra de Domicílios, National Survey from Home Sampling for the above period, as well as theorical econometric models. The empirical evidences, resulting from regression analysis, that will be presented through this work, show the existence of a relationship between the teachers that became union members and the students performance, mainly for the elementary school students.